HIDAYAT AL SALIKIN (Analisa Hadis Dalam MempengaruhiBudaya Melayu Palembang) - Sulaiman Mohammad Nur (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2016)
Shaykh 'Abd al-Samad al Falembaniy is scholar who also have a role to spread Islam in the archipelago. In order to combat irregularities and practice of religious teachings in the archipelago, he translated two works of al Ghazaliy‟s, Lubab Ihya 'Ulum al-Din and al Bidayat Hidayat. Two of these works present a system of Sufism at that time. Al Falembaniy also authored many books of Sufism, one of his works entitled Hidayat al Salikin. His contribution in Islamic thought has shown how his works have been